Rare bird documentation form for Peregrine Falcon at the north end of Saylorville Reservoir, 1985 - Dinsmore, Stephen J.et al (1985)
Rare bird documentation form for a Peregrine Falcon at the north end of Saylorville Reservoir in Polk County, IA on April 8, 1985. Epson - sheet feed